Influence of different surface modification treatments on silk biotextiles for tissue engineering applications - Ribeiro, Viviana P. (2017)
Biotextile structures from silk fibroin have demonstrated to be particularly interesting for tissue engineering (TE) applications due to their high mechanical strength, interconnectivity, porosity, and ability to degrade under physiological conditions. In this work, we described several surface treatments of knitted silk fibroin (SF) scaffolds, namely sodium hydroxide (NaOH) solution, ultraviolet radiation exposure in an ozone atmosphere (UV/O3) and oxygen (O2) plasma treatment followed by acrylic acid (AAc), vinyl phosphonic acid (VPA), and vinyl sulfonic acid (VSA) immersion. The effect of these treatments on the mechanical properties of the textile constructs was evaluated by tensile tests in dry and hydrated states. Surface properties such as morphology, topography, wettability and elemental composition were also affected by the applied treatments. The in vitro biological behavior of L929 fibroblasts revealed that cells were able to adhere and spread both on the untreated and surface-modified textile constructs. The applied treatments had different effects on the scaffolds' surface properties, confirming that these modifications can be considered as useful techniques to modulate the surface of biomaterials according to the targeted application.